2021
DOI: 10.1021/acssensors.1c00854
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Loaded Polymersome-Based Lateral Flow Assay: Rational Design of a COVID-19 Testing Platform by Repurposing SARS-CoV-2 Antibody Cocktail and Antigens Obtained from Positive Human Samples

Abstract: The global pandemic of COVID-19 continues to be an important threat, especially with the fast transmission rate observed after the discovery of novel mutations. In this perspective, prompt diagnosis requires massive economical and human resources to mitigate the disease. The current study proposes a rational design of a colorimetric lateral flow immunoassay (LFA) based on the repurposing of human samples to produce COVID-19-specific antigens and antibodies in combination with a novel dye-loaded polymersome for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The first step consisted of purifying highly sensitive antibodies from human samples through standard affinity-based methods. The produced antibodies were carefully characterized by various techniques such as ELISA, SDS-PAGE, LC-Q-TOF–MS/MS, and electrochemical analysis to validate the purity and functionality of the proteins [ 3 , 18 ]. The purified antibodies were conjugated with the synthesized PPy- g -PCL using succinic anhydride and EDC/NHS chemistries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step consisted of purifying highly sensitive antibodies from human samples through standard affinity-based methods. The produced antibodies were carefully characterized by various techniques such as ELISA, SDS-PAGE, LC-Q-TOF–MS/MS, and electrochemical analysis to validate the purity and functionality of the proteins [ 3 , 18 ]. The purified antibodies were conjugated with the synthesized PPy- g -PCL using succinic anhydride and EDC/NHS chemistries.…”
Section: Resultsmentioning
confidence: 99%
“…Their application covers a wide range of targets, including viral detection, substance use, toxins, environmental monitoring, food safety, and many others [ 2 ]. Immunoassays are qualitative and quantitative tools for detecting and measuring various targets based on the interaction between an antibody and a target antigen, making them a highly sensitive and selective instrument for diagnosis [ 3 ]. Immunoassay approaches have been integrated into many POC tests, such as paper-based assays (lateral flow assays and dot blots).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it helps predict immune response patterns that are necessary for developing prevention Placeholder TextPeptides with 7 amino acids or higher are considered as plausible sequences for further analyses methods. A more thorough study of the application of the current purified antigens and antibodies has been reported by our research group in our recent publication [13].…”
Section: Lateral Flow Assay Development For Diagnosticsmentioning
confidence: 98%
“…The color signal was provided by synthesizing a dyeloaded polymersome that was bioconjugated with the purified antibody cocktail and loaded with Coomassie blue dye. The detailed protocol for the biosensor's design, preparation, and application can be found in our recent work [13].…”
Section: Development Of a Paper-based Colorimetric Lateral Flow Assay For The Detection Of Sars-cov-2 Antigens And Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation